Ventriculoperitoneal shunt infections and re-infections in children: a multicentre retrospective study. (4th March 2018) - Yakut, Nurhayat; Soysal, Ahmet; Kepenekli Kadayifci, Eda; Dalgic, Nazan; Yılmaz Ciftdogan, Dilek; Karaaslan, Ayse; Akkoc, Gulsen; Ocal Demir, Sevliya; Cagan, Eren; Celikboya, Ezgi; Kanik, Ali; Dagcinar, Adnan; et al.
Abstract: Purpose: Ventriculoperitoneal shunt (VPS) is the most common treatment modality for hydrocephalus. However, VPS infection is a common and serious complication with high rates of mortality and morbidity. The objective of this study was to investigate causative agents and the management of VPS infections and to identify risk factors for re-infection in children. Materials and methods: Retrospective, multicentre study on patients with VPS infection at paediatric and neurosurgery departments in four tertiary medical centres in Turkey between January 2011 and September 2014. Results: A total of 290 patients with VPS infections were identified during the study period. The aetiology of hydrocephalus was congenital malformations in 190 patients (65.5%). The most common symptom of shunt infection was fever in 108 (37.2%) cases. At least one pathogen was identified in 148 VPS infections (51%). The most commonly isolated pathogen was coagulase-negative staphylococci, which grew in 63 cases (42.5%), followed by Pseudomonas aeruginosa in 22 cases (14.9%), Klebsiella pneumoniae in 15 cases (10.1%), and Staphylococcus aureus in 15 cases (10.1). The median duration of VPS infection was 2 months (range, 15 days to 60 months) after insertion of the shunt, with half (49.8%) occurring during the first month. VPS infection was treated by antibiotics and shunt removal in 211 cases (76.4%) and antibiotics alone without shunt removal in 65 patients (23.5%). Among the risk factors, CSF protein level greater than 100 mg/dL prior to VPS insertion was associated with a potential risk of re-infection (OR, 1.65; p  =.01). Conclusion: High protein levels (>100 mg/dL) before the re-insertion of a VPS may be a risk factor for VPS re-infection.